2006
DOI: 10.1016/j.chembiol.2006.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a Ribozyme to a Deoxyribozyme through In Vitro Evolution

Abstract: An RNA ligase ribozyme was converted to a corresponding deoxyribozyme through in vitro evolution. The ribozyme was prepared as a DNA molecule of the same sequence, and had no detectable activity. A population of randomized variants of this DNA was constructed and evolved to perform RNA ligation at a rate similar to that of the starting ribozyme. When the deoxyribozyme was prepared as an RNA molecule of the same sequence, it had no detectable activity. Thus, the evolutionary transition from an RNA to a DNA enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Similarly, DNA versions of some in vitro-selected RNA aptamers retain binding activity toward their targets (39). Additionally, a ribozyme ligase sequence was evolved into an active deoxyribozyme by only a few mutations (40). Finally, classical studies of various DNA-RNA chNA versions of the hammerhead ribozyme have demonstrated that some DNA substitutions can increase (41) or decrease activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, DNA versions of some in vitro-selected RNA aptamers retain binding activity toward their targets (39). Additionally, a ribozyme ligase sequence was evolved into an active deoxyribozyme by only a few mutations (40). Finally, classical studies of various DNA-RNA chNA versions of the hammerhead ribozyme have demonstrated that some DNA substitutions can increase (41) or decrease activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…The core octamer of the ribosomal peptidyl transferase is also the favored binding site sequence adjacent to a transition state analog for peptide bond formation (Yarus and Welch 2000). This implies that this core peptidyl transferase sequence came from selection on a molecule very like modern RNA (because RNA activities are usually disrupted by minor modification of their nucleotides [Paul et al 2006]). Similarly, in all four cases so far examined, successively squeezed selection shows that the simplest binding sites for Ile (Lozupone et al 2003), Trp , His , and Arg (Janas et al 2010) contain essential cognate coding triplets.…”
Section: Rna Chemistry and Evolutionary Questionsmentioning
confidence: 99%
“…Although there is no known example of a deoxyribozyme in nature, catalytic variants selected in vitro to perform peroxidations were observed for hemin aptamers (212). Alternatively, the translation of the catalytic function encoded by a ribozyme with RNA ligase activity into a deoxyribozyme can be obtained by directed in vitro evolution of the translated sequence (161). In this report, Joyce and coworkers demonstrate that the basic chemistry of the ribozyme catalytic activity could be detected in the evolved deoxyribozyme although the value of the catalytic parameters and the stereospecificity were not preserved.…”
Section: Protein Engineeringmentioning
confidence: 97%